ANALYSIS OF IMPLEMENTATION OF POVERTY REDUCTION POLICY THROUGH THE REHABILITATION OF UNLIMITED HOUSING ACTIVITIES (RTLH) IN TRIMULYO WARD SEMARANG CITY - Desy Kumala Dewi; Ari Subowo; Teuku Afrizal (Journal of Public Policy and Management Review, 2022)
The problem of poverty never ends to be discussed, especially on the issue of housing because basically the house is a housing need. In line with the Minister of Social Affairs Regulation Number 20 of 2017 concerning the Minister of Social Affairs Rutilahu and Sarling in order to overcome the problem of poverty, in it is implementation, especially the provision of assistance for R-RTLH activities in Trimulyo Village, Semarang City, there are still problems regarding not achieving the target number of houses to be rehabilitated. The aims of this research are: (1) to analyze the procedure or mechanism for the implementation of R-RTLH activity assistance in Trimulyo Village and (2) to analyze the driving and inhibiting factors for the implementation of R-RTLH activity assistance in Trimulyo Village. The method used in this study is a descriptive method with a qualitative approach with a focus on Research Implementation of R-RTLH Activities, and the locus of the Trimulyo Village, Semarang City and using the theory of policy implementation according to George C. Edwards III in the form of Communication, Resources, Disposition/Attityde Behavior, and Bureaucratic Structure. Data collection techniques with primary data collection in the form of interviews, field observations, and documentation. Determination of informants in this study using a purposive technique with 1 person from the Semarang City Housing and Settlement Service Office, Trimulyo Village Head, Genuk Sub-district Head, BKM Coordinator, Semarang City Gapensi Chair, 3 RT Chairs in Trimulyo Village, and 3 beneficiaries R-RTLH activities. The results of this study indicate that the implementation of assistance for R-RTLH activities in Trimulyo Village has not been optimal. The contributing factors are communication and socialization of activities that have nor been maximized, limited budget funds, lack of human resources, limited human resources skills, slow disbursement of funds, low community capacity for assistance, lacj of good response to the community, lack of consistency of implementers, and long acceptance of requests for assistance. Several efforts are needed, such as a serious commitment to carry out activities, as well as improving coordination and communication of the parties involved to synergize with each other so that activities run well and have a positive impact on poverty alleviation in Trimulyo Village, Semarang City.